CULTURAL DIVERSITY FOR SUSTAINABLE DEVELOPMENT IN ART AND DESIGN THROUGH NEW-AGE MEDIA - Jha, Aditi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Culture is a broad-spectrum term commonly used to identify habits of a heterogeneous social groups which develop in a specific geographic location. It is evidently reflected through the various art practices, be it visual or performing arts, or artifacts created by the artisans. They have become an integral part of the cultural ethos. India is a country rich in such diverse treasure of cultural practices through art. Artisans have also migrated beyond their original geographical boundaries to diversify the reach of the art. It is an important cultural asset which helps to preserve the culture and heritage of a community or the skill-sets of the artisans. Our ancestors have been preserving this culture of storytelling through the art forms which show a perspective of life. They also contribute to the livelihood of the craftsmen, thus contributing to the economy of the country. There is beauty in promoting cultural diversity; people learn new skills from other cultural groups and encourage innovation through various art forms and designs. In the contemporary era of technology, modernization and globalization, the traditional art forms are fading away. Sustainability of these valuable these art forms is a concern today. Purposes and functionality of these art practices have also diversified. The study creates new objectives through cultural diversity and designing new products for sustainable development in art and design. The article discusses some aspects of technological intervention in these art practices that can help sustain these heritages. Thus diversification of media, purpose and an involvement of the young generation can help to preserve the social cultural ethos of our country.